Gut Microbial Dysbiosis and Changes in Fecal Metabolic Phenotype in Precancerous Lesions of Gastric Cancer Induced With N-Methyl-N′-Nitro-N-Nitrosoguanidine, Sodium Salicylate, Ranitidine, and Irregular Diet - Chu, Fuhao; Li, Yicong; Meng, Xiangmei; Li, Yuan; Li, Tao; Zhai, Mengyin; Zheng, Haocheng; Xin, Tianxi; Su, Zeqi; Lin, Jie; Zhang, Ping; Ding, Xia (Frontiers in Physiology, 2021)
Background and Aims: PLGC is the most important pathological phase with increased risk of GC, and encompass the key stage in which the occurrence of GC can be prevented. In our previous report, we found that the gut microbiome changed significantly during the process of malignant transformation of chronic gastritis to GC in a MNNG multiple factors-induced rat model. However, the changes of gut microbiota and metabolites, inflammatory factors and their correlation in the formation of PLGC have not yet been revealed. Methods: In this study, MNNG, sodium salicylate drinking, ranitidine feed and irregular diet were used to establish a PLGC rat model. The pathological state of the gastric mucosa of rats, the main inflammatory cytokines levels in the serum, the microbial composition and metabolites in the stool samples were evaluated and the correlation analysis was performed to clarify their biological function. Results: The results showed that the gastric mucosa of the PLGC rats had obvious morphological and pathological malignant changes, and the serum levels of inflammatory cytokines, including IL-1β, IL-4, IL-6, IL-10, IFN-γ, TNF-α and M-CSF increased significantly, while the level of CXCL1 in serum significantly reduced. There were significant differences in the composition and fecal metabolic profiles of the gut microbiota between the PLGC and control rats. Among them, Lactobacillus and Bifidobacterium increased, while Turicibacter, Romboutsia, Ruminococcaceae_UCG-014, Ruminococcaceae_UCG-005 and Ruminococcus_1 were significantly reduced in the PLGC rats. Microbial populations, including Bifidobacterium, Akkermansia, Bacteroides, Faecalibaculum and Coriobacteriaceae_UCG-002, were greatly associated with the PLGC model group. The metabolites related to lipid metabolism and PPAR signaling pathway have also undergone significant changes. In addition, there were significant correlation between changes of inflammatory cytokines in the serum, fecal metabolic phenotype and gut microbial dysbiosis in PLGC rats. Conclusion: The activation of inflammatory response, disturbance of the gut microbiota and changes in fecal metabolic phenotype could be closely related to the occurrence of PLGC. The gut microbiota and metabolites may primarily regulate lipid metabolism and the PPAR signaling pathway to induce inflammation and the formation of the tumor microenvironment.